A Hermeneutic Introduction to Maps - Paolo Furia (Études Ricoeuriennes / Ricoeur Studies, 2021)
The aim of this article is to show how a Ricœurian approach to space and place is likely to raise issues about geography and even cartography, rather than just ontological topology in a Heideggerian fashion. Two steps will lead towards that conclusion: the first concerns the role of Ricœur’s long détour in the transition from a transcendental—therefore empty—notion of place to the concrete plurality of places, which turns them into matters for interpretation; the second shows how the task of interpreting of places implies distanciation and even objectification, through which they are constituted as objects of scientific and critical investigation. Maps will be introduced at that point as specific interpretations of places, halfway between text and images, between the subject and the object, and between science and art.